An analysis of relationship between quality of life indices and clinical improvement following intervention in patients with intermittent claudication due to femoropopliteal disease - Mazari, Fayyaz Ali Khan; Carradice, Daniel; Abdul Rahman, Mohd Norhisham Azmi; Khan, Junaid A.; Mockford, Katherine; Mehta, Tapan; McCollum, Peter T; Chetter, Ian C (Elsevier, 2010)
Objectives: To establish the relationship between quality of life (QOL) index scores and clinical indicators of lower limb ischemia. Methods: One hundred seventy-eight patients (108 men, median age 70 years) with femoropopliteal lesions suitable for angioplasty were recruited. Assessments were performed prior to and at 1, 3, 6, and 12 months following intervention (angioplasty and/or supervised exercise program). Clinical indicators of lower limb ischemia (treadmill walking distances, ankle pressures), generic (SF36, EuroQol), and disease-specific (Kings College VascuQol) quality of life questionnaires were analyzed. Correlation analysis was performed for index scores (SF-6D, EQ-5D, VascuQol) and individual domain scores using nonparametric tests. Results: All clinical indicators of lower limb ischemia and quality of life index scores showed a statistically significant improvement as result of intervention (Friedman test, P < .001). Both generic QOL index scores (SF-6D, EQ-5D) showed moderate but statistically significant correlation (Spearman’s rank correlation, P < .001) with treadmill walking distances (SF-6D r 0.533, EQ-5D r0.500) and weak but significant correlation to resting and postexercise ankle-brachial pressure index (SF-6D r0.253, EuroQol r 0.214). Disease-specific index scores (VascuQol) showed similar moderate correlation to treadmill walking distances (r 0.584, P < .001) and weak but statistically significant correlation with resting and postexercise ABPI (r 0.377, P < .001). All index scores showed strong and statistically significant (P<.001) correlation with patient-reported walking distance (SF-6D r 0.604, EQ-5D r 0.511, VascuQol r 0.769). All domains of SF36 showed similar correlation with clinical indicators except general health. The strongest correlation was seen with treadmill walking distances in the domains of physical function (r0.538) and bodily pain (r 0.524). Conclusion: All generic and disease-specific QOL scores show statistically significant improvement with angioplasty and/or supervised exercise in patients with claudication due to femoropopliteal atherosclerosis. However, the degree of improvement seen in clinical indicators of lower limb ischemia is not reflected in these scores. These findings support the use of composite outcome measures with mandatory, independent assessment of QOL as an independent outcome measure in intervention studies in these patients.